Pengaruh Ekonomi Politik Terhadap Perdagangan Internasional dan Pembangunan Ekonomi - M. Zuhriadi; Reneva Manurung; Rista Y. Lumbangaol; Bonaraja Purba (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to discuss the influence between political economy and international trade and economic growth. This research uses a qualitative method which aims to determine the impact that monetary and fiscal policies from the political economy can have on international traders and the economic growth of a country. In Indonesia, the government is focusing on infrastructure development as part of its New Political Economy (EPB) strategy to increase people's productivity and standard of living. It is hoped that through various financing innovations and private involvement, infrastructure development can continue in a sustainable manner. Indonesia's economic policy must continue to be directed towards inclusive and quality economic development, with the aim of reducing poverty, reducing inequality and increasing employment opportunities. It is hoped that the results of this research will increase readers' insight into the influence of political economy on international traders and economic growth.